The Cost Analysis of Green Construction Implementation in The Building Construction Project of The Institut Teknologi dan Bisnis Sabda Setia Pontianak - Dumanauw, Stefani; Lusiana, Lusiana; Syahrudin, Syahrudin (Jurnal Teknik Sipil, 2024)
Building construction projects often face challenges during construction and operation. Implementing green construction is a promising solution to enhance process efficiency. Green construction involves planning and executing projects focusing on efficient energy, water, cost usage, and construction waste management. This study analyzes the additional costs of applying green construction to the Institut Teknologi dan Bisnis Sabda Setia (ITBSS) building in Pontianak. Using market price data and Work Unit Price Analysis (AHSP), the estimated additional cost for implementing green construction indicators is Rp34,122,728.55. These costs include energy and water conservation, air quality, and environmental management. However, utilizing recycled materials reduces costs associated with land use. Green construction enhances project sustainability and efficiency, leading to significant long-term savings. While this research highlights the additional costs, it does not provide a detailed calculation of long-term benefits. The findings suggest that green construction practices are viable and sustainable, urging stakeholders to embrace these practices for improved project performance and environmental impact.